Settings of short left-turn lane and signal phase sequence for isolated signalized intersections - Yao, Ronghan (Transport, 2016)
At signalized intersections, short left-turn lanes are often installed to improve capacity and level of service. However, the blockage or overflow of short left-turn lane often occurs when signal phasing is not coordinated with lane configuration and traffic demands. On the basis of probability theory, the probability of no blockage and overflow of the short left-turn lane is formulated under the three common signal phase plans when the lane next to a short leftturn lane is a through lane. For this case, it is shown that the left-through phasing should be adopted for the study approach when the short left-turn lane is very short and the volume of left-turn vehicles is high enough, and the leading or lagging left-turn phasing should be adopted for the study approach when the short left-turn lane is long enough and the volume of left-turn vehicles is low enough. To optimally allocate the space for each short left-turn lane and the green time for each lane group, a new optimization model is put forward to maximize intersection capacity and guarantee an acceptable level of service for each movement for isolated signalized intersections with short left-turn lanes. The usage of this model is demonstrated by an illustrative example. The results indicate that the intersection capacity can be maximized under the same level of service by integrating the configuration of traffic lanes and the split of signal phases. Finally, the procedure for using the proposed model is given for practical applications. First published online: 28 May 2014